Minimizing Ischemia Reperfusion Injury in Xenotransplantation - Patel, Parth M.; Connolly, Margaret R.; Coe, Taylor M.; Calhoun, Anthony; Pollok, Franziska; Markmann, James F.; Burdorf, Lars; Azimzadeh, Agnes; Madsen, Joren C.; Pierson, Richard N. (Frontiers in Immunology, 2021)
The recent dramatic advances in preventing “initial xenograft dysfunction” in pig-to-non-human primate heart transplantation achieved by minimizing ischemia suggests that ischemia reperfusion injury (IRI) plays an important role in cardiac xenotransplantation. Here we review the molecular, cellular, and immune mechanisms that characterize IRI and associated “primary graft dysfunction” in allotransplantation and consider how they correspond with “xeno-associated” injury mechanisms. Based on this analysis, we describe potential genetic modifications as well as novel technical strategies that may minimize IRI for heart and other organ xenografts and which could facilitate safe and effective clinical xenotransplantation.